Factores responsables de la eutrofización en ecosistemas lacustres tropicales - Quijije Frías, Jereny Daniela (Machala : Universidad Técnica de Machala, 2022)
Lakes are aquatic ecosystems that cover 402 km2 of the earth's surface and their importance lies in the availability of water for human activities. Among the types of lakes, tropical lakes, characterized by temperatures above 20°C, stand out. The particular feature of lakes is the natural aging process caused by the constant deposition of sediments on the bottom, as a result of eutrophication caused by high nutrient concentration, shallow depth, scarce vegetation cover, runoff and geological characteristics, thus becoming a terrestrial ecosystem, a natural process that takes thousands of years. Anthropogenic activity has accelerated the aging of lake ecosystems mainly due to eutrophication, generally mediated by the use of agricultural fertilizers, industrial waste discharged into the water body, nitrogen released into the atmosphere from the burning of fossil fuels, etc. The trophic level of a lake can be determined by various assessment methods such as the Trophic State Index (TSI), among others. Eutrophication in lake ecosystems unbalances the habitat of species, bringing with it catastrophic consequences for all organisms active in the lake trophic chain, and for human health.
Los lagos son ecosistemas acuáticos que abarcan 402 km2 de la superficie terrestre y su importancia radica en la disponibilidad de agua para las actividades humanas. Entre los tipos de lagos destacan los tropicales, que se caracterizan por poseer temperaturas por encima de los 20°C. Lo particular de los lagos es el proceso natural de envejecimiento causado por la deposición constante de sedimentos en el fondo, producto de la eutrofización provocada por alta concentración de nutrientes, poca profundidad, escasa cobertura vegetal, escorrentía y características geológicas, con lo cual llega a convertirse en un ecosistema terrestre, proceso natural que toma miles de años. La actividad antropogénica ha acelerado el envejecimiento de los ecosistemas lacustres debido principalmente a la eutrofización, mediada generalmente por el uso de fertilizantes agrícolas, emisión de residuos industriales que se descargan al cuerpo de agua, nitrógeno liberado a la atmósfera por la quema de combustibles fósiles, etc. El nivel trófico en el que se encuentra un lago puede ser determinado mediante varios métodos de evaluación como por ejemplo, el TSI (Trophic State Index), entre otros. La eutrofización en los ecosistemas lacustres desequilibra el hábitat de las especies, trayendo consigo consecuencias catastróficas para todos los organismos activos en la cadena trófica lacustre, y para la salud humana.
Keywords: NUTRIENTES; ESTADO TRÓFICO; EUTROFIZACIÓN; LAGOS TROPICALES; ECOSISTEMA LACUSTRE